ANALISIS KESALAHAN KONSEPTUAL SISWA DALAM MENYELESAIKAN SOAL BARISAN DAN DERET ARITMATIKA DITINJAU DARI GAYA KOGNITIF - Pelo, Fatmawati Mirsa; Nihayah, Elok Faik Khotun; Hasman, Hasman (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2024)
This research aims to describe students' conceptual errors in solving problems and arithmetic series in terms of cognitive style and to determine the causal factors. This type of research is qualitative descriptive research. Checking the validity of the data uses triangulation techniques. The results of this research show that, conceptualization errors made by subjects with Field Dependent and Field Independent cognitive styles are: 1) not writing down important information from the questions, 2) not being precise in choosing the formula, 3) not being precise in applying the formula, and 4) not being precise enough correct in the calculation process. The contributing factors are: 1) Feeling that you have forgotten to write down important information from the questions, 2) Having a habit of answering questions, 3) Feeling that you already understand the solution process, 4) Not paying attention to the calculation process, 5) Lack of interest in learning mathematics, and 6) Being in a rush -Hurry in solving problems. The importance of this research is to prevent or minimize students from making the same mistakes in solving arithmetic sequences and series problems. Keywords: Conceptual Errors, Arithmetic Sequences and Series, Cognitive Style